2009
DOI: 10.1017/s1481803500011489
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe seizures from a posterior cerebral artery aneurysm presenting as memory flashbacks

Abstract: Memory flashbacks are usually attributed to recreational drugs or psychiatric conditions. The differential diagnosis for memory flashbacks is diverse and challenging; moreover, management is influenced by the working diagnosis. We describe the case of a 35-year-old man who presented with memory flashbacks secondary to temporal lobe seizures from an unruptured aneurysm of the posterior cerebral artery. To our knowledge, a case of this nature has not been previously reported. This case demonstrates the need to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Notably, seizure onset was focal in four cases. [7][8][9][10] Of these, awareness was described in two patients as being impaired and in one patient as intact.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, seizure onset was focal in four cases. [7][8][9][10] Of these, awareness was described in two patients as being impaired and in one patient as intact.…”
mentioning
confidence: 99%
“…A review of the literature identified five cases of patients with PCA aneurysms presenting with seizures (Table 1). [6][7][8][9][10] The median age was 30, with range between 7 weeks to 35 years. Unique to the present case, the patient is the oldest reported at 59 years of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation